Determinants of Sukuk Ratings in Indonesia: The Role of Financial Performance as a Moderator - Siska; Antoni R, Stevanus; Zulhelmy (Accounting Analysis Journal, 2025)
Purpose: The study examines the long-term influence of sukuk age, institutional ownership, and managerial ownership on sukuk ratings with financial performance as a moderating variable in sukuk issuing companies in Indonesia. Method: The population comprises 30 sukuk issuers during 2021-2023, from which 18 companies met the criteria using purposive sampling. Data analysis used the PVMAR and PVMECM techniques. Findings: The findings reveal that institutional ownership, managerial ownership, and financial performance have a long-term effect on sukuk ratings, while sukuk age does not. Moreover, financial performance strengthens the long-term effects of sukuk age, institutional ownership, and managerial ownership on sukuk ratings. Novelty: The study offers a new perspective on the interaction between sukuk rating determinants and financial performance in Indonesia, which provides essential implications for sukuk issuing companies in Indonesia to improve their financial performance. It shows the importance of good corporate governance and support from institutional shareholders as long-term stability factors that positively affect Sukuk ratings.